Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
[tex]\frac{N}{5}^{(2}-\frac{5N}{10}=\frac{1}{5}^{(2} -we \ bring \ to \ the \ same \ denominator \\\\\ 2N-5N=2 \\\\ -3N=2 \\\\ \boxed{N=-\frac{2}{3}}[/tex]
N/5 - 5N/10 = 1/5
Multiply each side by 10 :
2N - 5N = 2
Combine the left side: 2N - 5N = -3N
So the equation now says -3N = 2
Divide each side by -3 : N = -2/3
Multiply each side by 10 :
2N - 5N = 2
Combine the left side: 2N - 5N = -3N
So the equation now says -3N = 2
Divide each side by -3 : N = -2/3
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.